MANAJEMEN RISIKO KEUANGAN PADA UMKM MOCHI MAMI: IDENTIFIKASI, ANALISIS, DAN MITIGASI - Bunga Amira; Dian Farindah Damanik; Natasyah Natasyah; Wira Herdika Firliansyah P.H; Arsyadona Arsyadona (JOURNAL SAINS STUDENT RESEARCH, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy, contributing over 60% to the Gross Domestic Product (GDP) and employing a large portion of the workforce. However, MSMEs, including Mochi Mami, which specializes in mochi production, often face challenges in managing financial risks. This study aims to analyze the financial risks faced by Mochi Mami and provide recommendations for more effective management. The methodology involves qualitative analysis through unstructured interviews and secondary data collection. The results identify several risks, including irregular cash flow records, fluctuations in raw material prices, inconsistent revenues, and credit risks. A SWOT analysis evaluates Mochi Mami’s strengths, weaknesses, opportunities, and threats, which helps in formulating risk management strategies. Recommendations include improving financial record-keeping systems, diversifying products, and strengthening relationships with suppliers. With effective risk management, Mochi Mami is expected to enhance its financial stability and business sustainability.